Volumetric radiative properties of irregular open-cell foams made from semitransparent absorbing-scattering media. (February 2019) - Li, Yang; Xia, Xin-Lin; Sun, Chuang; Zhang, Shun-De; Tan, He-Ping
Highlights: Irregular open-cell foams generated from Voronoi tessellation. User-defined struts made from semitransparent absorbing-scattering media. Analytical model and predictive relations of effective radiative properties. MCRT simulation on tomographic structures from real ceramic foams. Normal transmittance measurement on real ceramic foams. Abstract: This study aims to fully investigate the volumetric radiative properties of irregular open-cell foams made from semitransparent absorbing-scattering media such as ceramics. A Monte Carlo ray-tracing model was established in the limit of geometric optics to extract volumetric radiative properties of foams generated by a Voronoi tessellation technique. Three shape parameters for struts were proposed to mimic real struts. It was found that for extinction coefficient, the most influent parameters are porosity, mean cell diameter, and cross-sectional shape. For scattering albedo, it no longer depends on the surface reflectivity of solid struts but on the component radiative properties and strut shape parameters. Similarly, the scattering phase function no longer depends on the local reflection type but on an integrated contribution of the surface reflection, interface refraction, and volumetric radiation propagation inside the struts. The asymmetry factor is found closely related to the transparency of struts. Using the component radiative properties and structural parameters as input parameters, three analytical relations were established to respectively predict the extinction coefficients, scattering albedos, and asymmetry factors, which can be useful for the design and application of open-cell foams made from semitransparent media. Graphical abstract: Image, graphical abstract